How Grades 4 to 8 Teachers Can Deliver Intensive Vocabulary and Reading Comprehension Interventions to Students With High-Functioning Autism Spectrum Disorder. (April 2020) - Cravalho, Danielle A.; Jimenez, Zaira; Shhub, Aya; Solis, Michael
This article discusses use of a multicomponent intervention to develop the reading skill and performance of grades 4 to 8 students identified with high-functioning autism spectrum disorder. Reading intervention targets for this population are vocabulary, fluency, and comprehension. Reading intervention elements involve explicit vocabulary instruction, repeated reading with sentence-level comprehension, question-answering relationships, and main idea summarization. Included in the article are explicit instructional routines and curricular materials supported by empirical evidence for the intervention elements.